Preoperative Hemoglobin A1c and the Occurrence of Atrial Fibrillation Following On-pump Coronary Artery Bypass Surgery in Type-2 Diabetic Patients. Issue 1 (March 2017) - Abbaszadeh, Shahin; Shafiee, Akbar; Bina, Payvand; Jalali, Arash; Sadeghian, Saeed; Karimi, Abbasali
Abstract : Background: We investigated the association of the preoperative hemoglobin A1c (HbA1c) with occurrence of postoperative atrial fibrillation (POAF) in type-2 diabetic patients who underwent isolated coronary artery bypass grafting. Methods: We prospectively studied 708 type-2 diabetes patients [433 men ([61.2%)], candidate for isolated coronary artery bypass grafting. Biochemistry profile was measured on the day of operation. All patients were telemonitored for 72 hours after operation for the occurrence of atrial fibrillation. The role of HbA1c as a predictor for the occurrence of atrial fibrillation was then evaluated. Results: A total of 109 (15.3%) patients developed POAF. Patients in the atrial fibrillation group tended to be older, with prolonged longer diabetes, and have renal failure, chronic obstructive pulmonary disease, and hypertension. In the univariable and multivariable regression model, HbA1c was not a predictor for POAF. Conclusions: Serum level of HbA1c could not be used as a predictor for the development of POAF.